2011
DOI: 10.1007/978-3-642-21898-9_43
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Game Based Learning Design

Abstract: Abstract. The standardization of the design of learning games is a contradictory topic: The existence of a rich variety of domains and applications is in conflict with the desire for unification that would result in improved reusability, interoperability and reduction of design complexity. In this paper, we describe the use of the ICOPER Reference Model (IRM) specification as foundation layer for the design of digital learning games. This reference model incorporates design and development processes as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
2
5
0
2
Order By: Relevance
“…The set of expert studies we conducted confirm our view that gamification concepts should also support intrinsic motivational factors, engagement, community-building and personalization. In line with previous results [37,[41][42][43][44][45], the designs created by our participants indicate that gamification can be helpful in education only if it is carefully selected and designed chosen according to the application scenario at hand (problem to be solved/addressed, target group, topic, domain, content).…”
Section: Discussionsupporting
confidence: 88%
“…The set of expert studies we conducted confirm our view that gamification concepts should also support intrinsic motivational factors, engagement, community-building and personalization. In line with previous results [37,[41][42][43][44][45], the designs created by our participants indicate that gamification can be helpful in education only if it is carefully selected and designed chosen according to the application scenario at hand (problem to be solved/addressed, target group, topic, domain, content).…”
Section: Discussionsupporting
confidence: 88%
“…On a technical level, a digital game is not dissimilar to any other large software development project, and therefore recognized models such as Boehm's spiral [41] are readily applicable. One perspective describes a serious game as an iterative, user-centric agile development project [42]; iteration is expressed as central in a range of methodologies for serious game development [43,44]. However, in its loosest form, iteration can be suggested as a solution to a wide range of issues; the problem is translating the iterative cycle into one sufficiently pragmatic for game development within resource constraints.…”
Section: Design Processes Supporting the Development Of Seriousmentioning
confidence: 99%
“…Games are often designed for a specific purpose (and not customisable) or they require specialised customisation skills (which can hardly be done by a teacher/educator, who is usually not a game designer or developer). In the Serious Games research field, an approach to help simplifying the design process for Serious Games is through applying a pattern-based approach as known from the branch of the entertainment games (Björk & Holopainen, 2004) and combining it with educational objectives (Kelle et al 2011). While this approach has also successfully been applied to mobile learning games (Schmitz, 2014), little is known on how to systematically apply game-design patterns to augmented reality.…”
Section: Serious Games and Game-design Patternsmentioning
confidence: 99%
“…"The pattern approach has increasingly been applied to other areas such as the domain of educational science by way of pedagogical patterns (Kohls & Wedekind, 2011), for example, or to the design of digital games" (Schmitz, 2014). The GDP approach, indeed, has been successfully used in Serious Games (Kelle, et al 2011) and Mobile Games (Schmitz, 2014) and in the literature examples of "Design Patterns supporting the Development of Mobile Mixed Reality Games" (Wetzel, 2013) are already available. Furthermore already in research the effects of AR solutions have been analysed, as will be shown in the next paragraph.…”
Section: Serious Games and Game-design Patternsmentioning
confidence: 99%